2006
DOI: 10.1086/507606
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar Emission from Type Ib and Ic Supernovae

Abstract: The presumed Wolf-Rayet star progenitors of Type Ib/c supernovae have fast, low density winds and the shock waves generated by the supernova interaction with the wind are not expected to be radiative at typical times of observation. The injected energy spectrum of radio emitting electrons typically has an observed index p=3, which is suggestive of acceleration in cosmic ray dominated shocks. The early, absorbed part of the radio light curves can be attributed to synchrotron self-absorption, which leads to cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
496
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(537 citation statements)
references
References 52 publications
39
496
2
Order By: Relevance
“…We note that the progenitor population of GRBs is also believed to produce type Ib/c supernovae, and whenever the latter are detected at radio wavelengths, the inferred density profile is consistent with a wind-like environment (e.g., Chevalier 1998;Berger et al 2002;Chevalier & Fransson 2006;Chakraborti et al 2015). However, we find that an ISM model is a better fit than a wind environment for this burst, as the latter overpredicts the radio emission before 2.5 days.…”
Section: Summary and Discussionsupporting
confidence: 52%
“…We note that the progenitor population of GRBs is also believed to produce type Ib/c supernovae, and whenever the latter are detected at radio wavelengths, the inferred density profile is consistent with a wind-like environment (e.g., Chevalier 1998;Berger et al 2002;Chevalier & Fransson 2006;Chakraborti et al 2015). However, we find that an ISM model is a better fit than a wind environment for this burst, as the latter overpredicts the radio emission before 2.5 days.…”
Section: Summary and Discussionsupporting
confidence: 52%
“…Given the uncertainties in the observations, we recommend the use of this expression to get an estimate of the mass-loss rate from a CEDEX progenitor. Note that this expression has similar scaling relations as Equation (23) of Chevalier & Fransson (2006). Hence, the mass-loss rate of SN 2009bb as determined using that equation by Soderberg et al (2010) remains approximately correct.…”
Section: Appendix D Extracting Blast Wave Parameters From Radio Obsermentioning
confidence: 58%
“…Particle acceleration at the gasdominated shock gives rise to the radio synchrotron radiation emission that is observed from Type Ib/c supernovae, including SN 2008D. Chevalier & Fransson (2006) found that for the conditions typically found in SNe Ib/c, the X-ray emission from the later interaction is dominated by nonthermal mechanisms (inverse Compton and synchrotron) as opposed to thermal emission.…”
Section: Early X-ray Emissionmentioning
confidence: 94%
“…Here we argue that the spectrum is diluted in the scattering atmosphere, so that a larger radiating region can be accommodated. In a model intended for SN 1994I, Chevalier & Fransson (2006) & Fransson (2006) model predicts a drop in X-ray luminosity after day 10 when the photospheric luminosity drops. However, the supernova was close to the detection limit of Chandra on day 10 (Soderberg et al 2008), making it difficult to check this prediction.…”
mentioning
confidence: 99%